2022
DOI: 10.1177/13591045211070181
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the parental reflective functioning questionnaire in Iranian mothers

Abstract: This study aims to examine the psychometric properties of the Persian version of the Parental Reflective Functioning Questionnaire (PRFQ) in mothers, a brief self-report measure that assesses parental mentalization capacity. To examine the factor structure and construct validity of the PRFQ, 430 mothers of 3–6-year-old children completed the Persian version of the PRFQ (Persian-PRFQ) along with the Emotion Regulation Checklist (ERC) and the Strengths and Difficulties Questionnaire (SDQ). Exploratory and confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
3
3
0
Order By: Relevance
“…The Cronbach’s alpha and McDonald’s omega coefficients of the PRFQ factors ranged from .76 to .87, indicating good reliability for each of the three subscales of the PRFQ. CMS and IC are consistent with other studies [ 20 , 21 , 23 , 24 , 29 ]. On the other hand, in some of them, Cronbach’s alphas for PM are lower than those for the remaining subscales [ 20 , 21 , 23 , 24 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The Cronbach’s alpha and McDonald’s omega coefficients of the PRFQ factors ranged from .76 to .87, indicating good reliability for each of the three subscales of the PRFQ. CMS and IC are consistent with other studies [ 20 , 21 , 23 , 24 , 29 ]. On the other hand, in some of them, Cronbach’s alphas for PM are lower than those for the remaining subscales [ 20 , 21 , 23 , 24 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…CMS and IC are consistent with other studies [ 20 , 21 , 23 , 24 , 29 ]. On the other hand, in some of them, Cronbach’s alphas for PM are lower than those for the remaining subscales [ 20 , 21 , 23 , 24 , 29 ]. In the Polish PRFQ, the PM subscale had a relatively higher Cronbach’s alpha than some other PRFQ adaptations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Following these modifications, the 3-factor model of the questionnaire showed adequate fit. The findings revealed that the questionnaire structure was saturated with 3 factors, which is consistent with the results of previous research (10,(19)(20)(21)(22).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, Mousawi and Bahrami Ehsan (19) proposed a 3-factor structure for PRFQ in Iran. By assessing the internal consistency of the factors, Cronbach's alpha coefficients were measured to be 0.68, 0.72, and 0.68, respectively.…”
Section: Discussionmentioning
confidence: 99%